Scalar operators equal to the product of unitary roots of the identity operator - Samoilenko, Yu. S.; Yakymenko, D. Yu. (Ukrains’kyi Matematychnyi Zhurnal, 2012)
We study the set of all γ C for which there exist unitary operators U_i such that U_1U_2 ... U_n = γ I and U_i^m_i = I, where m_i N are given.